Injury surveillance in male professional football; is medical staff reporting complete and accurate? - Bjørneboe, J.; Flørenes, T. W.; Bahr, R.; Andersen, T. E. (Scandinavian Journal of Medicine & Science in Sports, 2011)
Since the 2000 season, an injury surveillance system has been established to monitor injury risk and injury patterns in the Norwegian professional football league. The aim of this study was to assess the accuracy of routine injury registration performed by medical staff in professional football. The team medical staff completed injury registration forms on a monthly basis throughout the 2007 season (January-October). Players were interviewed at the end of the season (October/November) about all injuries that occurred from July through September. Thirteen of fourteen teams, 296 of 310 A-squad players were interviewed. An injury was recorded when a player was unable to take fully part in football training or match the day after injury. A total of 174 injuries were registered, 123 acute injuries and 51 overuse injuries. Of these, 141 were reported by medical staff and 122 by players. Eighty-nine injuries (51%) were registered using both methods, 52 (30%) by medical staff only and 33 (19%) by player interviews only. Prospective injury surveillance by team medical staff in Norwegian male professional football underestimates the incidence of time-loss injuries by at least one-fifth.